Increased Expression of microRNA-141-3p Improves Necrotizing Enterocolitis of Neonates Through Targeting MNX1 - Chen, Hui; Zeng, Lichun; Zheng, Wei; Li, Xiaoli; Lin, Baixing (Frontiers in Pediatrics, 2020)
Objective: MicroRNA-141-3p (miR-141-3p) has been investigated in various kinds of cancers. This research delves into the functions and regulatory mechanisms of miR-141-3p in necrotizing enterocolitis (NEC) of neonates. Methods: NEC tissues were obtained from neonatal mice, and subsequently expression of miR-141-3p and motor neuron and pancreas homeobox 1 (MNX1) was assayed via RT-qPCR. Moreover, the intestinal histopathological changes and histiocytic apoptosis were observed via hematoxylin and eosin (H&E) and TUNEL staining. The correlative inflammatory factors and oxidative stress markers were evaluated to uncover the influence of miR-141-3p in NEC tissues damage. Further, the relation between MNX1 and miR-141-3p was predicated, and the functions of MNX1 in inflammatory response and cell growth of IEC-6 cells were investigated. Results: Down-regulated miR-141-3p and up-regulated MNX1 were discovered in NEC tissues. Moreover, miR-141-3p clearly alleviated inflammation response and oxidative stress damage in NEC, which was achieved through regulating inflammatory cytokines (IL-1β, IL-6 and TNF-α) and oxidative stress markers (MPO, MDA and SOD) expression. MNX1 was forecasted as a target gene of miR-141-3p, meanwhile MNX1 overexpression overturned the influence of miR-141-3p in inflammatory response and cell growth process of IEC-6 cells. Conclusion: These explorations revealed that increased expression of miR-141-3p could improve the damage to intestinal tissues in NEC through targeting MNX1. The research might exhibit a neoteric therapeutic strategy for NEC.